Eye movements desensitization and reprocessing with finger movements and Elite mobile health software on guilt feeling of parents of children with autism: A randomized trial - Rashidi, Hadi; Sadeghian, Efat; Shamsaei, Farshid; Tapak, Leili; Seyedi, Mahdieh (Journal of psychiatric and mental health nursing, 2025)
Accessible Summary What is known on the subject? Taking care of an autistic child at home can be tough for parents. They struggle to balance caring for their child and other tasks. This can affect their emotional well‐being and cause guilt and other psychological problems. What does the paper add to existing knowledge? Eye movement desensitization and reprocessing with finger movements can reduce guilt in parents of autistic children. Eye movement desensitization and reprocessing with Elite mobile health software movements can reduce guilt in parents of autistic children. The bilateral eye stimulation method using finger movements has a more sustained impact than the Elite app's bilateral stimulation method. What are the implications for practice? Healthcare providers are encouraged to learn Eye Movements Desensitization and Reprocessing. Healthcare providers are encouraged to use these methods to help with psychological issues in children with autism. Psychiatric nurses are encouraged to utilize this treatment approach for parents of children with autism, as well as to help alleviate feelings of guilt more broadly. Introduction Caring for an autistic child at home can be challenging for parents, as it can make it difficult to balance their responsibilities. This imbalance can negatively affect the emotional well‐being of the caregiver and lead to feelings of guilt. While this is a known issue, there may be gaps in knowledge specific to Iran. In this study, a new method was introduced to address this issue. Aim This study aimed to examine the impact of desensitization with eye movements and reprocessing (EMDR) on reducing parental guilt among autistic children's families. We aim to examine the effectiveness of two different treatment methods. Methods This study involved 90 parents (60 mothers, 30 fathers) of autistic children randomly assigned to either an experimental or control group. The two experimental groups received a 45‐min intervention session once a week for 3 weeks, while the control group did not receive any intervention. Data on feelings of guilt was collected using a questionnaire. After 30 days, both groups took a follow‐up test. The data were analysed using statistical software. Results This study found that there were significant differences in guilt feelings among different groups of EMDR therapy and a control group. Specifically, no significant differences were observed in the mean guilt scores between the experimental and control groups at the pre‐intervention stage (p > .05). However, the experimental groups exhibited significantly lower mean guilt scores immediately after the intervention and 1 month later than the control group (p < .05). Immediately after the intervention and 1 month later, no significant differences were observed between the two experimental groups (p > .05). Conclusions The findings of this study demonstrate the efficacy of desensitization treatment using eye movements and reprocessing in reducing feelings of guilt among autistic children's parents. In the follow‐up phase, it seems that the two‐way stimulation method with finger movements is more effective than Elite software in terms of the continuity of the effect. Healthcare providers are encouraged to learn and use these methods to help prevent and treat psychological issues in autistic children.